2016
DOI: 10.1007/s11274-016-2114-4
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation and utility of Piptoporus betulinus fruiting bodies as a source of anticancer agents

Abstract: Piptoporus betulinus is a wood-rotting basidiomycete used in medicine and biotechnology. However, to date, no indoor method for cultivation of this mushroom fruiting bodies has been developed. Here we present the first report of successful production of P. betulinus mature fruiting bodies in artificial conditions. Four P. betulinus strains were isolated from natural habitats and their mycelia were inoculated into birch sawdust substrate supplemented with organic additives. All the strains effectively colonized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 22 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Cyranka et al demonstrated that the type of mycelial extract has an effect on the growth and viability of colon adenocarcinoma cells [ 8 ]. Moreover Pleszczyńska et al showed the anti-proliferative and anti-immigration properties of water and ethanol extracts from fruiting bodies against human cancer cells [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cyranka et al demonstrated that the type of mycelial extract has an effect on the growth and viability of colon adenocarcinoma cells [ 8 ]. Moreover Pleszczyńska et al showed the anti-proliferative and anti-immigration properties of water and ethanol extracts from fruiting bodies against human cancer cells [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ratio of log yield was estimated at 2.8–6.1%. The only report on indoor production of F. betulina fruiting bodies was given by Pleszczyńska et al (2016). In the study, four strains of F. betulina isolated from natural habitats were applied.…”
Section: Cultivationmentioning
confidence: 99%
“…The most promising ones were even further tested through clinical trials and polysaccharide K, known also as krestin or PSK, from Coriolus versicolor , has been officially used in Japan as an adjuvant for cancer treatment [ 16 , 17 ]. The cultivation of polypore species is challenging as in the case of F. betulina (Chaga) [ 18 , 19 ]. If not, collecting the most promising species from the wild can be properly arranged.…”
Section: Introductionmentioning
confidence: 99%